Implementasi Strategi Pembelajaran Berdiferensiasi dalam Meningkatkan Hasil Belajar IPAS di SD Muhammadiyah Kecamatan Ciledug - Apriyal Rinaldi; Muhamad Sofian Hadi (Universitas Muhammadiyah Bangka Belitung, 2025)
This study aims to describe the analysis of the implementation of differentiated learning strategies in IPAS learning in elementary schools in Ciledug subdistrict. The research subjects include principals, teachers, and students. This research uses a qualitative method with a phenomenological approach, and data collection techniques through observation, interviews, and documentation studies. Data analysis was conducted using Milles and Huberman's approach which includes data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation techniques. The results showed that the implementation of differentiated learning strategies in IPAS learning was carried out through the stages of planning, implementation, and evaluation. The implementation of differentiated learning in primary schools in Ciledug subdistrict has been running well, by paying attention to differentiation elements such as readiness, interest, and student learning profiles. Collaboration between teachers, principals and other parties continues to be optimized to create quality and inclusive learning. This strategy facilitates students to learn according to their needs and potential, thus supporting the achievement of optimal learning outcomes.